Intergrating Green Chemistry and Sustainable Engineering - Ul-Islam, Shahid (John Wiley & Sons, Incorporated, 2019)
Over the past decade, the population explosion, rise in global warming, depletion of fossil fuel resources and environmental pollution has been the major driving force for promoting and implementing the principles of green chemistry and sustainable engineering in all sectors ranging from chemical to environmental sciences. It is noteworthy to mention that production of biofuels, exploitation of renewable energy sources and use of ecologically safer products in applied sectors are becoming increasingly important for the development of alternative sustainable technologies. Integrating Green Chemistry and Sustainable Engineering focusses on latest sustainable technologies and developments and describes how sustainable chemistry and engineering practices are being applied and integrated in various industrial sectors. The book addresses emerging topics including biofuel production, CO2 conversation to green fuels, advanced green polymers in coating applications, biological macromolecules in medical sector, biofertilizers for agricultural sector, bioadsorption and much more.